Bezacube web based application systems - Ahmad Syazwan, Ahmad Tarmizi (2013)
Nowdays, the increasing fame of social networking has bought a convenience to human life. Many people rely on the social network as a communication tool to obtain the information from around the world. Basically, this web based is a combination of catalogue product and Social network. In addition this web based is intended to serve human as a tool to fulfill their desires where they can choose any product they like and share it with their friends. By viewing Bezacube web based application, the customer will able to explore more product around their placed